The great race - O'Malley, Kevin, 1961- (New York : Walker & Co., 2011)
Retells the traditional tale of the tortoise and the hare as a match between the very vain Lever Lapin and Nate Turtle, who is tired of all of the publicity Lever's speed generates.
Booklist
Publisher's Weekly
School Library Journal
Booklist, April 2011
Publisher's Weekly, April 2011
School Library Journal, May 2011
Keywords: Fables; Folklore; Fables; Folklore; Fables; Folklore; Fables; Folklore; Picture books for children